Evolutionary ecology - Eric R Pianka (Harper Collins, 1994)
The book features balanced coverage of both plant and animal evolution. It deals with speciation, metapopulations, self-deceit, experimental ecology, modern comparative methods, null models, landscape ecology, macroecology, biodiversity, genetic engineering, equilibrium economics, and other aspects of applied ecology. The book is liberally illustrated with comprehensive tables and graphs to reinforce topics